(untitled) (Tribhuvan Journal, 2025)
Wild boar (Sus scrofa Linnaeus, 1758) is considered a major challenge to agricultural products for socio-economic loss. The study was conducted between June 2024 and April 2025. This study measured the level of crop destruction by wild boar, the cause, and local mitigation approaches in Rainadevi Chhahara Rural Municipality, Palpa. Data collection involved field observations, household surveys, interviews, and structured questionnaires in affected areas. Results showed maize, paddy, wheat, and potatoes were the most damaged crops, with maize suffering the greatest losses. Key factors influencing crop damage included proximity to forests, wild boar population density, seasonal crop availability (especially high in summer and autumn), and nighttime conditions. Mitigation strategies include crop guarding, group guarding, chasing with dogs, the use of noise and light, and physical barriers, where personal and group crop guarding methods were most effective. Integrated, community-based mitigation strategies supported by local communities and conservation organisations are essential for reducing crop losses and promoting sustainable coexistence between farmers and wild boars in the region.